EXEMPTION PROVISIONS AND THE CONSUMER PROTECTION ACT, 2008: SOME PRELIMINARY COMMENTS - Mark Tait; Stephen Newman (Obiter, 2014)
Suppliers have found it most convenient to reduce their risk of liability by inserting a provision in their contracts with consumers – be it in a written and signed contract or in the form of a displayed notice – in terms of which suppliers are exempted from liabilities they would otherwise be obliged to accept. Exemption of liability provisions are often contained in standard-form contracts but also in notices displayed at public venues such as hotels, restaurants, shopping malls, parking garages, entertainment complexes, tourist attractions and even petrol-service stations. The same may probably be said of a host of other suppliers, including suppliers of tourism services. It is not surprising, therefore, that a significant factor in the development of consumer law in general can be “ascribed to legislative responses to business disclaimers of accountability for negative consequences attendant upon their dealings with consumers”. The Consumer Protection Act 68 of 2008 (CPA) introduced a number of provisions which impact on the use by suppliers of provisions that aim to exclude the liability of suppliers for harm to consumers caused through the negligence of the supplier. The CPA defines a supplier in section 1 as: “a person who markets any goods or services”. To market is defined as: “to promote or supply any goods or services”. This note seeks to provide a conceptual framework for the understanding and application of relevant provisions of the CPA to exemption provisions. The impact is considered within the context of the tourism industry in order to illustrate some of the practical consequences of the CPA on the use of exemption provisions. The note does not seek to question whether exemption provisions are contrary to public policy per se.